Fenomena Anak Jalanan di Kota Makassar dan Problematika yang Dihadapi - Almaida Almaida; Andi Eka Putri O. A.; Zulkifli Zulkifli; M. Ridwan Said Ahmad; Ibrahim Arifin (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The problem of street children is a problem that has become a problem in every city, especially big cities like Makassar. The problem that is present actually arises in children in the underage age group who have to feel the harshness of life on the streets. Busking, begging, selling, and committing crimes to survive. Being a street kid is not a desirable option for everyone, especially when it comes to safety. Street children are often considered a problem, and there are no regulations that can overcome this phenomenon. This study used a literature study to explore the causes, life order, and vulnerabilities faced by street children who tend to behave deviantly. The results of the study showed that the existence of street children was caused by poverty, personality deviations, and external factors of the child. They have their own living order and are often regarded as the scum of society. Street life that is not conducive and lack of supervision from the family makes street children very vulnerable to various forms of violence. Therefore, to overcome the problem of street children, a complete change is needed so that they do not return to live and work on the streets again.